2005
DOI: 10.7773/cm.v31i12.98
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterization of surficial sediments from the southwestern Iberian continental shelf

Abstract: The impact of trace elements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 8 publications
0
19
0
4
Order By: Relevance
“…In its lower course, the Tinto River flows through Tertiary sedimentary formations made up mainly of clays and marls, which contain detritic and biogenic carbonates (Galán et al, 1999(Galán et al, , 2003Machado et al, 2005). In addition, authigenic gypsum has been identified in surface sediments of the estuary (Fernández-Caliani and Galán, 1997).…”
Section: Geochemical Modeling: Speciation-solubility and Reaction-patmentioning
confidence: 97%
“…In its lower course, the Tinto River flows through Tertiary sedimentary formations made up mainly of clays and marls, which contain detritic and biogenic carbonates (Galán et al, 1999(Galán et al, , 2003Machado et al, 2005). In addition, authigenic gypsum has been identified in surface sediments of the estuary (Fernández-Caliani and Galán, 1997).…”
Section: Geochemical Modeling: Speciation-solubility and Reaction-patmentioning
confidence: 97%
“…The coast of Huelva is considered as a heavily contaminated area where the Tinto Rivers (Machado et al, 2005). Pb contamination of the study area is related to sulfide minerals outflow which, besides wastes from the industrial complex located at the junction of the two rivers, contribute to considerable lead input to the marine environment (Martins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Las actividades mineras que aumentan la concentración de metales, tales como los elementos de las tierras raras y el polvo de cerámica, se consideran fuentes antropogénicas de itrio. En el suroeste de la Península Ibérica, el efecto de los procesos mineros estudiados en los sedimentos de un núcleo (163 mg Y kg -1 , Borrego et al 2004) mostraron un enriquecimiento de este elemento y una disminución hacia la costa continental (Machado et al 2005). Debido a su poca participación en reacciones diagenéticas, se utiliza como trazador de suelos y sedimentos a partir de las rocas originales (Munrad 1978).…”
Section: Methodsunclassified
“…Anthropogenic sources of Y include mining of rare earth and ceramic dust. Studies of southwestern Iberian Peninsula rivers showed that mining activities caused the enrichment of this element in estuarine sediments, with the highest content in core sediments of 163 mg kg -1 (Borrego et al 2004), and decreasing towards the continental shelf (Machado et al 2005). Because of its little involvement in early diagenetic reactions, Y has been used for tracing soils and sediments back to the parent rocks (Murad 1978).…”
Section: Introductionmentioning
confidence: 99%